Alcuni spunti di comparazione tra diritto italiano e diritto ebraico in tema di maternità surrogata (Stato, Chiese e pluralismo confessionale, 2018)
SOMMARIO: 1. Il divieto di maternità surrogata nell’ordinamento italiano - 2. Diritto ebraico e bioetica - 3. “Crescete e moltiplicatevi”. Il precetto divino di procreare e la maternità surrogata nel diritto ebraico - 4. Conclusioni.Some starting points for comparison between Italian law and Jewish law on surrogate motherhoodABSTRACT: Recent scientific progress in reproductive biotechnologies implies significant transformations in terms of the value and culture of the concept of maternity, which is no longer attributable to the legal definition of “mother” offered by Italian civil legislation. Assisted reproductive technologies separate the reproductive aspect and sexual union of the couple, finally leading to the metamorphosis of the relational dynamics underlying the “family identity” and the birth of new types of biolegal contracts. The study sets out to compare the approach that the Italian legal system reserves for the phenomenon of surrogacy with that which has developed at the heart of Jewish law. The interesting variety of opinions of the rabbinical authorities, which express both the Orthodox positions and the more progressive ones, show how Jewish speculation around bioethical reproductive issues has led to a respectful comparison of knowledge and judgements of the minority opinions that enter, with equal dignity, into the legal debate and are enhanced by the absence of a superior interpretation.